Local Wisdom in Chemistry Learning: A literature Review on The Ethnoscience Approach - Vika Puji Cahyani; Dewiyanti Fadly (Jurnal Studi Guru dan Pembelajaran, 2024)
The main issues in this research are how to integrate local wisdom into chemistry learning, its impact on students' understanding and skills, the challenges faced in its implementation, and the potential of local wisdom as a resource to improve the quality of chemistry education. The purpose of this study is to analyse the implementation of ethnoscience in chemistry learning at school. This research method uses a qualitative descriptive method with a literature review approach to examine local wisdom in learning chemistry through an ethnoscience approach. The steps taken in this research are determining the topic and problem formulation, data collection, literature analysis, synthesis of findings and preparation of conclusions. The results showed that the integration of local wisdom into chemistry learning has shown a positive impact on students' skills and understanding. Several studies have highlighted the importance of incorporating local wisdom as it has the potential to increase students' interest and motivation in learning chemistry. Students become more engaged and active in the learning process when they see the relevance of chemistry materials to their daily lives. The implementation of ethnoscience in chemistry learning in schools has many potential benefits, but still faces various challenges. Teachers face various challenges in implementing ethnoscience, including lack of resources and supportive teaching materials, lack of training and support from the school, as well as difficulties in adapting the existing curriculum to the ethnoscience approach.